2015
DOI: 10.1039/c5ra16339k
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the radical reaction mechanism in the cross-linking process of polyethylene

Abstract: The mechanism of the valerophenone voltage stabilizer for increasing the electrical breakdown strength of cross-linked polyethylene is expected to provide reliable information to prepare insulation material for high voltage cables up to 500 kV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Table 3 lists the calculated values of the vertical and adiabatic IPs and EAs at the B3LYP/6-311+G(d,p) level and the corresponding experimental data 32 (in bracket), as well as the calculated HOMO-LUMO energy gap (E g ). The B3LYP//6-311+G(d,p) level was conrmed to be suitable for the current study since the computational values of the adiabatic ionization potentials IP(a) and the electron affinities EA(a) at this level are in agreement with the corresponding experimental values in our previous study, 33 which indicates that the theoretical results herein are reasonable and reliable. The varied trends of the IP and EA are similar to that for the negative value of the corresponding HOMO and LUMO energies, respectively.…”
Section: Energies: Frontier Mos Ips and Eassupporting
confidence: 71%
“…Table 3 lists the calculated values of the vertical and adiabatic IPs and EAs at the B3LYP/6-311+G(d,p) level and the corresponding experimental data 32 (in bracket), as well as the calculated HOMO-LUMO energy gap (E g ). The B3LYP//6-311+G(d,p) level was conrmed to be suitable for the current study since the computational values of the adiabatic ionization potentials IP(a) and the electron affinities EA(a) at this level are in agreement with the corresponding experimental values in our previous study, 33 which indicates that the theoretical results herein are reasonable and reliable. The varied trends of the IP and EA are similar to that for the negative value of the corresponding HOMO and LUMO energies, respectively.…”
Section: Energies: Frontier Mos Ips and Eassupporting
confidence: 71%
“…The transition state was identified by having only one imaginary frequency. This level of B3LYP/6-311+G( d , p ) has been proved to be suitable for current research in our previous paper where the calculated results are consistent with the corresponding experimental results [26]. The time-dependent density functional theory (TDDFT) method [27,28] was employed to calculate the excitation energies of two kinds of polar molecules on the basis of the optimized geometries at the B3LYP/6-311+G( d , p ) level.…”
Section: Methodsmentioning
confidence: 68%
“…This compound effectively inhibited electrical tree initiation and showed improved compatibility with XLPE; however, it did not inhibit the migration of voltage stabilizers. Zhang et al found by theoretical calculation that acetophenone doping in XLPE or grafting onto XLPE molecule chains can suppress electrical tree initiation and propagation and enhance the breakdown strength [28,29]. We propose to address the problem of voltage stabilizer migration by grafting the voltage stabilizer onto XLPE, which to our knowledge has not been previously reported.…”
Section: Introductionmentioning
confidence: 98%